Implementation of Green Accounting and Disclosure of Corporate Social Responsibility on Company Performance - Bleskadit, Novalia Herlina; Paru, Sara Marlyn (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study will use a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) as well as industrial companies that have received the Green Industry Award from the Ministry of Industry, with an observation period of three years, namely 2020, 2021, and 2022. The Green Industry Award is a program that recognizes industrial companies implementing green industry principles in their production processes, with the aim of motivating companies to adopt and apply these principles. The purpose of this research is to examine the effect of green accounting implementation and corporate social responsibility (CSR) disclosure on company performance, specifically financial performance and environmental performance. Financial performance will be measured using profitability ratios, while environmental performance will be measured using the PROPER index. The research population consists of manufacturing companies listed on the IDX. The sampling technique applied is purposive sampling, namely manufacturing companies that publish annual reports, CSR disclosures, sustainability reports, and Global Reporting Initiative (GRI) index disclosures, as well as those participating in the PROPER program. The type of data used in this research is secondary data